The Protection Effect of Centella asiatica L.Urban extract on the Kidney Histological Structure of Mice (Mus musculus ) induced by toxic doses of paracetamol - Berlian Permata Sakti; Muthmainah .; Ratih Puspita Febrinasari (Nexus Biomedika, 2015)
Background: Centella asiatica L.Urban contains antioxidant compounds such as triterpenoid, essential oil and flavonoid. The compounds have significant activities to reduce oxidative stress that can make damage of kidney cells. This study aimed to investigate protection effect of Centella asiatica L.Urban extract on the kidney histological structure of mice (Mus musculus ) induced by toxic doses of paracetamol. Method: This study was an experimental laboratory research. Samples were 30 mice, Swiss webster type, 2-3 weeks old and 20 grams of weight. Samples were divided into 5 groups, each group consisted of 6 mice (Mus musculus). The control group (KK) was given no treatment, just regular feed. Induction group (KI) was induced by paracetamol but did not get any treatment, just got distilled water. KP1, KP2, and KP3 groups induced by paracetamol got treatment with Centella asiatica L.Urban extract at a dose of 5 mg, 10 mg and 20 mg per 20 gram of body weight. Kidney histological damage were assessed by the sum of the cell nucleus pyknosis, karyorrhexis, and karyolysis. Data were analyzed using one-way ANOVA and post hoc multiple comparison test. Result: The ANOVA test for all groups showed that p value was 0.000 (p < 0.05). The post hoc multiple comparisons test showed the significant differences between group KK-KI, KK-KP1, KK-KP2, KK-KP3, KI-KP1, KI-KP2, KI-KP3, KP1-KP2, KP1-KP3, and KP2-KP3. Conclusion: Centella asiatica L.Urban extract has a protection effect to kidney histological structure of mice (Mus musculus) induced by paracetamol. Keyword : Centella asiatica L.Urban, paracetamol, kidney damage.